Estrategia de marketing internacional para potenciar el desempeño exportador de las pymes agrícolas de El Oro. - Cuenca Villacres, Nathalia Yolanda; Maza Choez, Jeniffer Lissette (Machala : Universidad Técnica de Machala, 2022)
The participation of SMEs influences the economic development of Ecuador, because they are the ones that generate the most economic movement and increase the employment rate; Ecuadorian agricultural SMEs provide milk, onion, cocoa, bananas, coffee, eggs, among others, despite their great reach at the national level, they present limitations when entering international trade through exports. This is due to lack of managerial skills, financial conditions and application of marketing strategies. To this end, this paper has the following general objective: Promote the export performance of agricultural SMEs in El Oro through the study of international marketing strategies.The type of study according to its gnoseological objective is descriptive with a qualitative paradigm, theoretical methods such as analytical-synthetic and inductive - deductive, hypothetical-deductive and abstraction - concretion were used for the theoretical foundation of the research, analyze international marketing strategies and the contributions of results. The empirical methods that were used were the survey and the study of documents and the materials used were documents obtained from databases and the closed survey.The results indicate that the case studies investigated through the application of marketing strategies enhanced their export performance, through the management and positioning of the brand, content dissemination, innovation and quality, in addition, the agricultural SMEs surveyed use marketing strategies. international only with the advertising function, without taking advantage of the other resources. The international marketing strategies studied are media strategies, competitive strategy, standardization strategy, and marketing mix.For this purpose, it is concluded that international marketing channels the impulse of the export performance of agricultural SMEs, through the correct application of the strategies and it is recommended that agricultural SMEs use media, competitive and marketing mix strategies.
La participación de las pymes influye en el desarrollo económico del Ecuador, porque son las que más generan movimiento económico y aumentan la tasa de empleo; las pymes agrícolas ecuatorianas aportan leche, cebolla, cacao, banano, café, huevos, entre otros, a pesar de su gran alcance a nivel nacional, presentan limitaciones al momento de entrar al comercio internacional mediante la exportación. Esto se debe a falta de habilidades gerenciales, condiciones financieras y aplicación de estrategias de mercadotecnia. A tal efecto, el presente trabajo planteó el siguiente objetivo general: Potenciar el desempeño exportador de las pymes agrícolas de El Oro mediante el estudio de estrategias de marketing internacional. El tipo de estudio según su objetivo gnoseológico es descriptivo con un paradigma cualitativo, se usaron métodos teóricos como el analítico– sintético e inductivo – deductivo, hipotético- deductivo y abstracción – concreción para la fundamentación teórica de la investigación, analizar las estrategias del marketing internacional y los aportes de resultados. Los métodos empíricos que se usaron fueron la encuesta y el estudio de documentos y los materiales usados fueron documentos obtenidos de bases de datos y la encuesta cerrada. Los resultados indican que los casos de estudios investigados mediante la aplicación de estrategias de marketing potenciaron su desempeño exportador, a través de la gestión y posicionamiento de la marca, difusión de contenidos, innovación y calidad, además las pymes agrícolas encuestadas utilizan las estrategias de marketing internacional solo con la función de publicidad, sin aprovechar los demás recursos. Las estrategias de marketing internacional estudiadas son estrategias de medios, estrategia competitiva, estrategia de estandarización y marketing mix. A tal efecto, se concluye que el marketing internacional canaliza el impulso del desempeño exportador de las pymes agrícolas, mediante la correcta aplicación de las estrategias y se recomienda a las pymes agrícolas el uso de las estrategias de medios, competitiva y marketing mix.
Keywords: MARKETING; DESEMPEÑO; COMERCIALIZACIÓN; PYMES